Sherlock. Season four [videorecording (Blu-Ray)] - Talalay, Rachel, 1958-; Hurran, Nick; Cumberbatch, Benedict, 1976-; Freeman, Martin, 1971-; Graves, Rupert, 1963-; Doyle, Arthur Conan, 1859-1930 (BBC, 2017)
In twenty-first-century London, Sherlock Holmes solves cases that stump Scotland Yard, assisted by his friend Dr. John Watson.